LEVEL OF ESTROGEN HORMONE AND ESTRUS PERFORMANCE OF DIFFERENT POSTPARTUM ESTRUS OF JAWA RANDU GOAT - Tanjung, A. D.; Setiatin, E. T.; Samsudewa, D. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The purpose of this research was to determine the reproductive quality of normal compared withabnormal postpartum estrus (PPE) of Jawa Randu Goats (n = 16 goats) on estrogen hormon level andestrus profile. Total samples were 16 Jawa Randu goats. The data were analyzed descriptively and nonparametric data were analyzed using Mann Whitney U-test of Statistical Package for the Social science(SPSS) 16. Descriptive statistics was used on estrogen hormone and resulting that normal postpartumestrus (PPE) Jawa Randu Goats had a better level (133.8; 141.5; 155.6; 162.25; 167.75 pg/mL)compared with abnormal postpartum estrus of Jawa Randu Goat (109.9; 111.35; 101.2; 132.2; 142.45pg/mL). Mann Whitney U-test used for the abundance of cervical mucus and ferning showed nonsignificantly different of postpartum estrus between both groups. Jawa Randu goats with normal PPEhad a higher estrogen level than abnormal PPE goats. However, for the abundance and ferning ofcervical mucus, between the two groups of goats was not different.